Advancing Complexity Research in Earth Sciences and Geography - Gao, Jianbo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In order to solve richer and more diverse problems in environmental and Earth sciences and other fields that have a direct impact on human society and human life, it has become a global trend to synergistically utilize methodological innovations in all relevant fields, including statistical science, systems science, complexity science, and artificial intelligence, to tackle the problems. This Reprint, a collection of papers published in a Special Issue of Applied Sciences, demonstrates the feasibility of such a rationale. This Special Issue is hoped to instigate further activities along this line.